Perspective of Medan City Scholars on the Law of Wives who Demand Divorce from Husbands with Disabilities Due to Accidents - Muhammad Hafiz Antassalam; Ibnu Radwan Siddik Turnip (JUSTITIA JURNAL HUKUM, 2024)
When a couple is legally married, both have their own rights and responsibilities. The husband, as the leader of the household, acts as the main protector. However, what if the husband loses physical ability due to an accident, so the wife sues for divorce? According to Article 39 of Law No. 1 Year 1974 and Article 110 of the Compilation of Islamic Law (KHI), divorce due to the disability of one of the spouses is allowed if it makes it difficult to fulfil household obligations. However, some Nahdlatul Ulama scholars in bahsul masail consider a wife who sues for divorce from a disabled husband as an act of nusyuz (defiance). This study aims to examine the views of Medan City scholars regarding wives who sue for divorce from husbands who become disabled due to accidents. This empirical research collected primary data from in-depth interviews with scholars in Medan. The results show that divorce is permissible if the husband's disability is severe and causes major impacts, such as abuse or neglect of the wife and children. In such cases, the husband's management responsibility is returned to his family.